The Impact of Eco-Friendly Behaviors on Life Satisfaction - LEELAKULTHANIT, Orose (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019, 2019)
In order to protect today’s deteriorating environment, various environmentally-friendly behaviors are necessary. The question is how desirable they are. It is the intention of this study to investigate this relationship by looking at the influences of eco-friendly behaviors on life satisfaction. The identified eco-friendly behaviors in this study are energy savings, avoiding buying unnecessary things, reusing, recycling, buying longer-life products even if they are more expensive, buying eco-friendly products even if they are more expensive, buying products from social and environmentally-responsible companies, and living a simple life. A total of 560 responses were collected from adult shoppers in Bangkok, Thailand. The results of the multiple regression analysis indicated that energy savings and buying longer-life products even if they are more expensive were positively related to life satisfaction. However, avoiding buying unnecessary things was found to be negatively related to life satisfaction. Further discussion and analysis will be included in the article.